Researching children's individual empathic abilities in the context of their daily lives: the importance of mixed methods - Roerig, Simone; van Wesel, Floryt; Evers, Sandra; Krabbendam, Lydia (Frontiers in Neuroscience, 2015)
In social neuroscience, empathy is often approached as an individual ability, whereas researchers in anthropology focus on empathy as a dialectic process between agents. In this perspective paper, we argue that to further elucidate the mechanisms underlying development of empathy, social neuroscience research should draw on insights and methods from anthropology. First, we discuss neuropsychological studies that investigated empathy in inter-relational context. Second, we highlight differences between the social neuroscience and anthropological conceptualization of empathy. Third, we introduce a new study design based on a mixed method approach, and present initial results of one classroom that was part of the larger study and included 28 children (m=13, f =15). Participants (age 9-11) were administered behavioral tasks and a social network questionnaire; an observational study was conducted during a period of 10 - 14 weeks. Initial results showed how children’s expressions of their empathic abilities were influenced by situational cues in classroom processes. This effect was further explained by children’s position in the classroom network. Our results emphasize the value of interdisciplinary research in the study of empathy.